The European Union, Civil Society and Conflict. - Tocci, Nathalie (Taylor & Francis, 2011)
Until recently, the European Union tended to view violent mass conflicts predominantly through the lens of negotiations between conflict leaders and powerful external actors. Today, the EU has begun to recognize the imperative of understanding and influencing developments on the ground in conflict situations by engaging with local civil society.The European Union, Civil Society and Conflict explores the EU's relations with civil society organizations at the local level, in an effort to improve the effectiveness and relevance of its conflict and peace strategies. Looking in p.